Konsep Pendidikan Karakter Presfektif Al-Ghazali dan Abdullah Nashin Ulwan - Yuliana Wardanik; Devy Habibi Muhammd; Ari Susandi (Edumaspul: Jurnal Pendidikan, 2021)
Writing this journal aims to find out how the thought of the concept of character education from the two Sufistic figures, namely Imam Al Ghazali and Abdullah Nashih Ulwan. Imam Al Ghazali's character education methods, exemplary methods, advice, stories, while the similarities and differences of Imam Al Ghazali are more spiritual, while the concept that Abdullah Nasih Ulwan is promoting is basic and general in nature and in accordance with the education of his time. While the similarities of thought of the two figures are that the ultimate goal of an education is to reach the level of taqarrub, then the similarities of the two figures are in the method section, namely the method of exemplary, advice, stories / stories and habituation.